Yukawa Potential Orbital Energy: Its Relation to Orbital Mean Motion as well to the Graviton Mediating the Interaction in Celestial Bodies. (1st January 2019) - Martz, Connor; Van Middelkoop, Sheldon; Gkigkitzis, Ioannis; Haranas, Ioannis; Kotsireas, Ilias
Abstract : Research on gravitational theories involves several contemporary modified models that predict the existence of a non-Newtonian Yukawa-type correction to the classical gravitational potential. In this paper we consider a Yukawa potential and we calculate the time rate of change of the orbital energy as a function of the orbital mean motion for circular and elliptical orbits. In both cases we find that there is a logarithmic dependence of the orbital energy on the mean motion. Using that, we derive an expression for the mean motion as a function of the Yukawa orbital energy, as well as specific Yukawa potential parameters. Furthermore, various special cases are examined. Lastly, expressions for the Yukawa rangeλ and coupling constantα are also derived. Finally, an expression for the mass of the gravitonm g r mediating the interaction is calculated using the expression its Compton wavelength (i.e., the potential rangeλ ). Numerical estimates for the mass of the graviton mediating the interaction are finally obtained at various eccentricity values and in particular at the perihelion and aphelion points of Mercury's orbit around the sun.